Effects of Neuromuscular Training on Performance and Injury Prevention in Youth Team Sports: Development of an Evidence-Based Educational Program - Markus Tschopp; Nicklaus Hess; Pascal Andrey; Adrian Rothenbühler; Fabian Studer (Current Issues in Sport Science)
Introduction Team sports have become increasingly fast-paced and athletic, particularly at the elite international level. Over the past 15 years, a widening performance gap in explosiveness and speed has been observed between Swiss youth and elite athletes in team sports. Promising talents with deficits in these areas face growing difficulties in establishing themselves at the elite level. Concurrently, there has been a rapid increase in scientific publications demonstrating the positive effects of neuromuscular training on explosiveness, speed, and in addition on injury prevention.